Application of a Twin Model for Monitoring and Predictive Diagnosis of Calle Calle Bridge in Chile. Issue 2 (October 2020) - Real, J; Márquez, M; Colomer, E; Labrado, M; Unión, A
Abstract: This study has developed a twin model tool that allows evaluating the current state and future behaviour of the Calle Calle bridge in Chile. The development of this twin model began with a finite element numerical model that was subsequently calibrated with data from sensors installed on the bridge. ANSYS APDL software was used to represent the structure by means of finite elements. The parameters captured by the sensors were the inclination and settlement in the abutments, the instantaneous deflection, and the proper frequencies. Calibration was an iterative process that sought to obtain a model that behaved similarly to the real structure. The twin model developed describes the reality of the structure allowing the simulation of future scenarios, thus improving the efficiency of management tasks, and thus achieving predictive maintenance. From the analysis carried out, it is concluded that the structure is in an acceptable state, requiring some maintenance. A great sensitivity of the bridge beams was also observed, which did not meet the current design criteria.